SOME FACTORS INFLUENCING THE INCOME OF KALIGESING GOAT FARMERS IN BOROBUDUR SUBDISTRICT, MAGELANG REGENCY, CENTRAL JAVA, INDONESIA - Setiadi, A.; Santoso, S.I.; Nuswantara, L.K.; Sunarso, S. (Diponegoro University, 2012)
The objectives of study to determine the income is obtained by Kaligesing goat farmer and todetermine the effect of some factors on the income. Survey method was conducted in this study, 47(forty seven) farmers in Giripurno village, Borobudur subdistrict, Magelang regency through interviewand observation. Secondary and primary data were obtained to answer the objective. Respondentcharacteristic, total revenue, total cost production, and total income were observed for 6 monthsobservation. Descriptive analysis and one sample t-test was used to analyze the data. Path analysis withTETRAD IV was used to determine the model. Dairy goat farmer in the study area rear goat were 10heads on average. Total revenue obtained was IDR 4,975,500, Total cost spent was IDR 1,865,200, andTotal income was IDR 3,110,300. Milk price and quality of the milk have influenced the number of milksold. The number of milk sold has influenced the income significantly. Milk price has influenceddirectly to the income while quality of milk has not directly influenced the income of farmer. Hence,improvement of quality of goat milk through diet manipulation is needed.